2018
DOI: 10.1140/epjc/s10052-018-5852-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving sensitivity of a BEGe-based high-purity germanium spectrometer through pulse shape analysis

Abstract: We performed Pulse Shape Analysis to separate single-scattered gamma energy deposition events from multiple-scattered photons in a high-sensitivity γ -ray spectrometer. The spectrometer is based on a Broad Energy High Purity Germanium detector and the developed technique uses multivariate analysis by an application of the Multi-Layer Perceptron Neural Network. A very good separation of the single-site-and multi-site events was achieved leading to a significant reduction of the background level of the investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…By analyzing survival probabilities in SEPs and FEPs it can be concluded that for this prototype detector the ANN-based PSA provides better multi-site events rejection efficiency. A similar behaviour was observed for the analysis described in [20]. However, it should be noted that for much more massive (≈ 0.5 kg−0.7 kg) BEGe detectors used in Gerda the A/E method provides much better multi-site events rejection efficiencies [17] as obtained here.…”
Section: Application Of Psa To the 228 Th Spectrumsupporting
confidence: 85%
See 4 more Smart Citations
“…By analyzing survival probabilities in SEPs and FEPs it can be concluded that for this prototype detector the ANN-based PSA provides better multi-site events rejection efficiency. A similar behaviour was observed for the analysis described in [20]. However, it should be noted that for much more massive (≈ 0.5 kg−0.7 kg) BEGe detectors used in Gerda the A/E method provides much better multi-site events rejection efficiencies [17] as obtained here.…”
Section: Application Of Psa To the 228 Th Spectrumsupporting
confidence: 85%
“…In the γ -ray spectrometry the situation is different: as the signal one considers MSEs (characteristic for the full energy peaks used to evaluate the activities) and SSEs, like e.g. the Compton scattered γ -rays contributing to the continuum need to be rejected as background events [20].…”
Section: Pulse Shape Analysismentioning
confidence: 99%
See 3 more Smart Citations